Analisis penerapan sistem dan prosedur pengeluaran kas belanja langsung pada Badan Pendapatan Daerah Provinsi Sulawesi Utara - Sambali, Ellyssa Belinda; Tinangon, Jantje J.; Lintong, Diana N. (Yayasan Widyantara Nawasena Raharja, 2024)
Implementing cash disbursement systems and procedures in accordance with applicable regulations is very important for government institutions in order to assess the effectiveness of the systems and procedures implemented and facilitate the cash disbursement process. The cash disbursement system and procedures are regulated in Minister of Home Affairs Regulation Number 77 of 2020 concerning Technical Guidelines for Regional Financial Management as well as being the main reference in managing regional cash at the Regional Revenue Agency of North Sulawesi Province. This research aims to analyze the implementation of systems and procedures for direct cash expenditure (LS) for the procurement of goods and services at the Regional Revenue Agency of North Sulawesi Province based on Minister of Home Affairs Regulation No. 77 of 2020. The type of research used is descriptive qualitative with data collection techniques through interviews, observation and documentation studies. The research results showed that the system and procedures for disbursing cash directly to the BAPENDA of North Sulawesi Province were running well in accordance with Minister of Home Affairs Regulation No. 77 of 2020.